Higher Long‐Term Visit‐to‐Visit Blood Pressure Variability Is Associated With Severe Cerebral Small Vessel Disease in the General Population - Xinyu Zhao; Ying Hui; Jing Li; Xian‐Quan Shi; Shuohua Chen; Han Lv; Shouling Wu; Zhenchang Wang (The Journal of Clinical Hypertension)
ABSTRACT Long‐term visit‐to‐visit blood pressure (BP) variability is linked to various diseases, but its impact on cerebral small vessel disease (cSVD) burden, and its features remains uncertain. We analyzed 1284 participants from the Kailuan cohort (2006–2022). Visit‐to‐visit systolic BP (SBP), diastolic BP (DBP), and pulse pressure (PP) variability were categorized into tertiles (low, middle, high). Magnetic resonance imaging identified white matter hyperintensities (WMH), lacunae of presumed vascular origin (LA), cerebral microbleeds (CMBs), and visible perivascular spaces (PVS). Total cSVD burden was classified as none (0), mild (1), moderate (2), or severe (3–4) based on the presence of these features. Logistic regression estimated odds ratios (ORs) and 95% confidence intervals (CIs). High SBP variability was associated with moderate cSVD burden (OR = 1.89, 95% CI: 1.09–3.29) and PVS (OR = 1.62, 95% CI: 1.10–2.39). High DBP variability was associated with LA (OR = 1.74, 95% CI: 1.06–2.84). High PP variability showed a significant risk for severe cSVD burden (OR = 2.49, 95% CI: 1.34–4.63). These associations were modified by age and hypertension status. Among young adults (age < 60 years), high PP variability was associated with severe cSVD burden (OR = 3.33, 95% CI: 1.31–8.44), LA (OR = 3.02, 95% CI: 1.31–6.93), and PVS (OR = 1.86, 95% CI: 1.20–2.88). The risk effects of SBP and PP variability on cSVD burden were significant only in participants with hypertension. High long‐term visit‐to‐visit BP variability (BPV), particularly in combination with hypertension, is a significant risk factor for total cSVD. Special attention should be given to PP variability in younger adults.